"I know I didn't ask for it, but I've got it and I've let my kids down": A secondary data analysis of qualitative maternal perspectives of their and adolescent children's unmet needs through a cancer diagnosis. (April 2023) - Rodriguez, Leonor; Dolan, Pat; Kerin, Michael; Groarke, AnnMarie
Abstract: Purpose: This article is a secondary data analysis which explores maternal unmet needs and their perception of the 'unmet needs' of adolescent children when they experienced maternal cancer. The analysis is underpinned by the theoretical framework of the Offspring Cancer Needs Instrument OCNI, (Patterson et al., 2013). Method: A secondary data analysis was carried out with ten maternal interviews analyzed using a deductive Thematic Analysis. This was to identify maternal unmet needs as well as their perceptions of their adolescent children's unmet needs and determine whether the OCNI framework was suitable to identify unmet needs of mothers and adolescent children in an Irish context. Results: The study found cancer is a challenging emotional burden for both mothers and their adolescent children. Emotions related to cancer recurrence were particularly difficult to deal with. Mothers struggle to identify the unmet needs of adolescent children and recognize that they lack the skills to approach the children, which adds to the burden of their illness burden and feelings of guilt. Conclusions: The study highlights the need to provide safe spaces for patients and adolescent children to deal with their emotions, strengthen relationships and improve communication associated with maternal cancer as these have a significant impact in their lives and may lead to tension and conflict within families. Highlights: Cancer is a challenging experience for children and families. Mothers and adolescents struggle to cope with the emotions evoked by cancer. Mothers lack awareness of their adolescent's unmet needs. Mothers need more skills and support to meet their adolescents' needs.